(untitled) (CIPEEX, 2025)
This research project aimed to evaluate tooth discoloration caused by root canal filling pastes used in pediatric dentistry. Blocks from bovine lower incisor crowns were prepared. A 2 mm thick remnant of enamel and dentin was obtained. The blocks were randomly distributed into 2 groups, according to whether or not dentin hybridization was performed. After hybridization, the blocks were subdivided into 5 experimental groups, according to the type of endodontic cement: 1) Guedes Pinto Paste; 2) Zinc oxide and eugenol paste; 3) Calcium hydroxide paste, prepared with p.a. calcium hydroxide and propylene glycol; 4) Paste containing Chloramphenicol + tetracycline chloride + zinc oxide and eugenol; 5) Vitapex®. Color determination was performed with a digital spectrophotometer, and measurements were obtained 7, 30, and 60 days after material placement. Data regarding discoloration were tabulated and tested for normality using the Shapiro-Wilk test. ANOVA and Tukey tests were employed. Filling paste and evaluation period showed a statistical difference in tooth color change (p< 0.05). Root canal filling pastes induce staining in the tooth structure.